An ode to Salonika : the Ladino verses of Bouena Sarfatty - Melammēd, Rene Lēwîn (Indiana series in Sephardi and Mizrahi studies, 2013)
Twentieth-century Salonika and Bouena's Ladino coplas -- Bouena's Ode to Salonika -- Tradition versus modernity and historical developments -- Coplas written by Bouena Sarfatty Garfinkle about life in Salonika -- The miseries that the Germans inflicted on Salonika -- Coplas about the miseries that the Germans inflicted on Salonika, 1941-1943